High hepatitis C virus infection among female sex workers in Viet Nam: strong correlation with HIV and infection drug use - Linh-Vi N Le; Siobhan O'Connor; Tram Hong Tran; Lisa Maher; John Kaldor; Keith Sabin; Hoang Vu Tran; Quang Dai Tran; Van Anh Thi Ho; Tuan Anh Nguyen (World Health Organization Regional Office for the Western Pacific, 2019)
Objective: The World Health Organization's guidelines on viral hepatitis testing and treatment recommend prioritizing high prevalence groups. Hepatitis C virus (HCV) infection disproportionately affects people who inject drugs and men who have sex with men, but data on female sex workers (FSW) are limited. The study aimed to determine active HCV infection and risk factors associated with HCV exposure among Vietnamese FSW. Methods: We surveyed 1886 women aged ≥ 18 years from Haiphong, Hanoi and Ho Chi Minh City who had sold sex in the last month. We tested for HCV antibody and HCV core antigen as markers for exposure to HCV and active infection, respectively. Results: Across these provinces, high prevalence of HCV exposure (8.8-30.4%) and active infection (3.6-22.1%) were observed. Significant associations with HCV exposure were HIV infection (aOR = 23.7; 95% CI: 14.8-37.9), injection drug use (aOR = 23.3; 95% CI: 13.1-41.4), history of compulsory detention (aOR = 2.5; 95% CI: 1.4-4.2) and having more than 10 sex clients in the last month (aOR = 1.9; 95% CI: 1.2-3.2). Among FSW who reported never injecting drugs, HIV infection (aOR = 24.2; 95% CI: 14.8-39.4), a history of non-injection drug use (aOR = 3.3, CI: 1.8-5.7), compulsory detention (aOR = 2.2; 95% CI: 1.2-4.0) and having over 10 sex clients in the last month (aOR = 2.2, 95% CI: 1.3-3.7) were independently associated with HCV exposure. Discussion: FSW have elevated HCV risks through sex- and drug-related pathways. These findings highlight the need to offer FSW-targeted HCV interventions and ensure their access to HIV prevention and treatment.